Analysis Of The Quality Of Services Of The Bpjs Program With The Level Of Satisfaction Of Husbands In Material Patients At Alita Medika Balongbendo Clinic Sidoarjo Year 2020 - Indra Noviani; Arina Chusnatayaini (Journal for Research in Public Health, 2021)
Quality is a dynamic condition that affects service products, people, processes and the environment that meet or exceed expectations. So that the definition of service quality can be interpreted as an effort to fulfill the needs and desires of consumers and the accuracy of their delivery in balancing consumer expectations (Tjiptono, 2015 in Dr. Oscarius Y.A. Wijaya, M.H., M.M., 2020). Based on the results of an initial study conducted by researchers using a questionnaire in February 2020 at the Alita Medika Clinic Balongbendo Sidoarjo on 10 husbands of maternity patients using the BPJS program, it shows that there are still many patient husbands who are dissatisfied.The research design in this study was correlational with a cross-sectional approach. The population in this study were all husbands of childbirth patients who came using the BPJS program to deliver their wives at the Alita Medika Clinic Balongbendo Sidoarjo in 2020. Samples were taken using a total Accidental technique, totaling 23 respondents. The independent variable in this study was Quality with an Ordinal scale. , and the dependent variable is Satisfaction with Ordinal scale. The research was conducted in May - June 2020 at the Alita Medika Clinic Balongbendo Sidoarjo in 2020. How to collect data using questionnaire interviews and MCH books which were processed by editing, coding, scoring, tabulating, data entry and cleaning. Data were analyzed using the Spearman rank test. From the results of the Spearman Rank test above, it shows a significance value of 0.006 which means that there is a relationship between x and y because <0.05, the correlation coefficient above is positive, namely 0.551, so it can be said that the relationship between the two variables is unidirectional. Thus it can be interpreted that the higher the quality of BPJS services, the greater the satisfaction of the husband and mother giving birth. The conclusion is that the relationship between the quality of BPJS services and the satisfaction of husbands and mothers in giving birth is quite strong. According to Budiastuti's opinion (2002 in Nirmala Arum, 2020) suggests that patients in evaluating satisfaction with the services received refer to several factors, one of which is the quality of service factor. In general, it is stated that what is meant by quality health services is health services that can satisfy every user of health services in accordance with the average level of satisfaction of the population, and whose implementation is in accordance with the established code of ethics and professional service standards.